The Polyphosphate Kinase Gene ppk2 Is Required for Mycobacterium tuberculosis Inorganic Polyphosphate Regulation and Virulence - Yu-Min Chuang (American Society for Microbiology, 2013)
ABSTRACT The Mycobacterium tuberculosis gene Rv3232c/MT3329 (ppk2) encodes a class II polyphosphate kinase, which hydrolyzes inorganic polyphosphate (poly P) to synthesize GTP. We assessed the role of ppk2 in M. tuberculosis poly P regulation, antibiotic tolerance, and virulence. A ppk2-deficient mutant (ppk2::Tn) and its isogenic wild-type (WT) and complemented (Comp) strains were studied. For each strain, the intrabacillary poly P content, MIC of isoniazid, and growth kinetics during infection of J774 macrophages were determined. Multiplex immunobead assays were used to evaluate cytokines elaborated during macrophage infection. The requirement of ppk2 for M. tuberculosis virulence was assessed in the murine model. The ppk2::Tn mutant was found to have significantly increased poly P content and a 4-fold increase in the MIC of isoniazid relative to the WT and Comp strains. The ppk2::Tn mutant showed reduced survival at day 7 in activated and naive J774 macrophages relative to the WT. Naive ppk2::Tn mutant-infected macrophages showed increased expression of interleukin 2 (IL-2), IL-9, IL-10, IL-12p70, and gamma interferon (IFN-γ) relative to WT-infected macrophages. The ppk2::Tn mutant exhibited significantly lower lung CFU during acute murine infection compared to the control groups. ppk2 is required for control of intrabacillary poly P levels and optimal M. tuberculosis growth and survival in macrophages and mouse lungs. IMPORTANCE Mycobacterium tuberculosis, the causative agent of tuberculosis (TB), is a highly successful human pathogen because it has developed mechanisms to multiply and survive in the lungs by circumventing the immune system. Identification of virulence factors responsible for M. tuberculosis growth and persistence in host tissues may assist in the development of novel strategies to treat TB. In this study, we found that the mycobacterial enzyme polyphosphate kinase 2 (PPK2) is required for controlling intracellular levels of important regulatory molecules and for maintaining susceptibility to the first-line anti-TB drug isoniazid. In addition, PPK2 was found to be required for M. tuberculosis growth in the lungs of mice, at least in part by suppressing the expression of certain key cytokines and chemokines by inactivated lung macrophages.